2014
DOI: 10.11648/j.ijnfs.20140305.26
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Composite Bread Produced from Wheat, Defatted Soy and Banana Flours

Abstract: Abstract:The physicochemical and sensory evaluation of the bread produced from the composite flour of wheat, defatted soy and banana was determined. Five bread samples were produced from the proportion of wheat/defatted/banana composite flours as 90%:5%:5% (B), 80%:10%:10% (C), 70%:15%:15% (D), 60%:20%:20% (E) and 100% wheat was the control sample (A). The crude protein, crude fibre, moisture and ash contents of the composite breads increased significantly (P<0.05) with increase in the proportion of defatted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
(11 reference statements)
2
8
1
Order By: Relevance
“…The replacement of 20% BP hadn't different significant, but it improved sensory properties, the results of mean values were (5.9, 4.7, 4.7) respectively compared to control (4.8, 4.8, 5.9). These results go parallel with Dooshima et al [34] whose studied quality evaluation of composite bread produced from wheat, defatted soy and banana flours, it showed that bread from the composite flours of 20% substitution for both defatted soy and banana flours were accepted. According to the study of Eshak NS [55] about sensory evaluation and nutritional value of balady flat bread supplemented with banana peels as a natural source of dietary, she showed that replacing bread at 10% BP was accepted as sensory evaluation and nutritional value.…”
Section: Resultssupporting
confidence: 79%
“…The replacement of 20% BP hadn't different significant, but it improved sensory properties, the results of mean values were (5.9, 4.7, 4.7) respectively compared to control (4.8, 4.8, 5.9). These results go parallel with Dooshima et al [34] whose studied quality evaluation of composite bread produced from wheat, defatted soy and banana flours, it showed that bread from the composite flours of 20% substitution for both defatted soy and banana flours were accepted. According to the study of Eshak NS [55] about sensory evaluation and nutritional value of balady flat bread supplemented with banana peels as a natural source of dietary, she showed that replacing bread at 10% BP was accepted as sensory evaluation and nutritional value.…”
Section: Resultssupporting
confidence: 79%
“…No significant difference was seen in the overall acceptability of refined wheat flour and little millet flour and later with that of soy and gluten added bread. The sensory analysis results were similar to those reported by Dooshima et al, (2014) for wheat, soy and banana composite flour bread.…”
Section: Sensory Quality Of Breadsupporting
confidence: 88%
“…; Dooshima et al. ). Horse gram ( Dolichus uniflorus ) commonly known as Gahat is a traditional unexploited tropical grain legume, a cheapest source of protein and a good source of calcium, iron, and molybdenum, however, it is deficient in methionine and tryptophan as other legumes (Kadam and Salunkhe ; Bhokre et al.…”
Section: Introductionmentioning
confidence: 97%